CONSIDERATIONS REGARDING THE APPLICATION OF THEORY IN PROBLEM SOLVING SPATIAL PROJECTION OF INTERSECTIONS OF SIMPLE OBJECTS - Mihaela Cotrumba; Alexandru Pintilie (Journal of Industrial Design and Engineering Graphics, 2015)
This paper presents how descriptive geometry contributes to the achievement of intersections of simple objects and isometric axonometric representation of these intersections. It also highlights the role of descriptive geometry on acquiring skills in Technical Drawing, in representation of objects intersection. All illustrations in this paper are made using Microsoft Office Word Drawing Toolbar and AutoCAD software.